2000
DOI: 10.1073/pnas.040558497
|View full text |Cite|
|
Sign up to set email alerts
|

An advanced glycation endproduct cross-link breaker can reverse age-related increases in myocardial stiffness

Abstract: Decreased elasticity of the cardiovascular system is one of the hallmarks of the normal aging process of mammals. A potential explanation for this decreased elasticity is that glucose can react nonenzymatically with long-lived proteins, such as collagen and lens crystallin, and link them together, producing advanced glycation endproducts (AGEs). Previous studies have shown that aminoguanidine, an AGE inhibitor, can prevent glucose cross-linking of proteins and the loss of elasticity associated with agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
195
3
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(214 citation statements)
references
References 16 publications
10
195
3
4
Order By: Relevance
“…Alternatively, AGE-directed therapy can consist of so-called AGE-breakers (64). Thiazolium compounds such as N-phenacylthiazolium bromide and phenyl-4,5-dimethylthiazolium chloride, which have been reported to break dicarbonyl-containing AGEs, showed efficacy in reversing AGE-related tendon crosslinking and cardiac stiffness (65,66). Despite the fact that these therapies are relatively new, they provide proof that inhibition or reversal of AGE formation can have beneficial effects in AGE-mediated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, AGE-directed therapy can consist of so-called AGE-breakers (64). Thiazolium compounds such as N-phenacylthiazolium bromide and phenyl-4,5-dimethylthiazolium chloride, which have been reported to break dicarbonyl-containing AGEs, showed efficacy in reversing AGE-related tendon crosslinking and cardiac stiffness (65,66). Despite the fact that these therapies are relatively new, they provide proof that inhibition or reversal of AGE formation can have beneficial effects in AGE-mediated pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…Proof for the involvement of AGEs in structural stiffness remains fairly indirect but has been fueled by animal and a recent clinical trial found that a breaker of AGE (ALT-711) improves vascular distensibility, 52,53 and perhaps ventricular diastolic distensibility ( Figure 5A). 54 Last, we recently reported that enhancement of protein kinase G activation by inhibiting PDE5a may provide a novel approach to ventricular-arterial stiffening. 55 PDE5a is the enzymatic target of sildenafil, which is widely used to treat erectile dysfunction.…”
Section: Destiffening Strategiesmentioning
confidence: 99%
“…In diabetic rats, collagen III was found to decrease, collagen solubility to increase, and RAGE and AGE-R3 mRNA levels to decrease when compared to the animals receiving vehicle after 4 weeks of treatment with ALT-711 [11,12]. In vivo studies showed that ALT-711 improves LV function, decreases ventricular collagen, and decreases the rigidity of LV in elder diabetic rats with increasing the survival time [13,14].…”
Section: • Toprak Et Al In Vitromentioning
confidence: 92%